Other Research – Alcohol and Substance Use by Adolescents and Young Adults with Recent Spinal Cord and Traumatic Brain Injuries - Block, Pamela; Bock, Beth; Becker, Bruce; Everhart, Sarah (Disability Studies Quarterly, 2001)
Alcohol and substance use constitute a significant health risk for people with disabilities. Rates of alcohol and substance use are higher among individuals with disabilities, often play a contributing role in the onset of injury-related disability, and severely disrupt the effectiveness of post-injury rehabilitation. This ethnographic study of 24 youths participating in a 5-week residential rehabilitation program confirms a high prevalence of problematic use of alcohol and substances that create psychological and physiological barriers to rehabilitation. Family history and pre-injury alcohol and substance use were common among study participants; however, social needs appeared to significantly contribute to continued alcohol and substance use. This paper presents the results of this research employing individual case examples to explore these dimensions of alcohol and substance use among college-age youths with disabilities and discusses opportunities for alcohol and substance use intervention.